International Military Training and Education for a Long-Term Defense Capacity Building: NATO & Ukraine - Savero, Vito; Swastanto, Yoedhi; Timur, Fauzia Gustarina Cempaka (PT FORMOSA CENDEKIA GLOBAL, 2024)
It has been more than a year since Russia launched a military operation against Ukraine in February 2022. Russia’s military operation is still on-going as Ukraine fights vigorously. Russia is among the most powerful countries in the world by military and experts argue that Kremlin hugely underestimates Ukraine’s resistance. It is notable that Ukraine has been forging a partnership with the North Atlantic Treaty Organization (NATO) since 1991 because they perceive Russia as their common enemy. The fact that Ukraine has managed to be undefeated by Russia so far opens the possibility that their partnership, which manifests for example in the form of long-term military training and education, has helped Ukraine to build its defense capacity the country required to deal with present security challenges. The research finds that NATO-Ukraine collaboration in enhancing Ukraine's defense capabilities has positive impacts on building Ukraine’s readiness in dealing with its security issues, although geopolitical complexities, internal dynamics, and resource constraints exist as challenges Ukraine needs to overcome to continue enhance its defence capacity.